(untitled) (Economic and Political Thought, 2018)
Particular political parties’ manifestoes constitute crucial elements of public discourse. On the one hand, they are an emanation of the views held by political parties and their voters, on the other hand, they form a basis for political competition between particular formations, both during electoral campaigns and in the periods between the elections. In the Polish political reality, proposals concerning foreign policy make one of pivotal elements of those political programmes. The article aims to present the results of the research into the place of Russia and Polish-Russian relations in the programmes of the most important political formations operating in Poland. The author also attempts to review the political programmes for their specificity as well as their internal structures and the nature of the proposals that they include. As a result of the quantitative analysis, it has been concluded that the relations with Russia constitute a crucial element in the political programmes proposed by the majority of significant Polish political parties. The qualitative analysis has made it possible to distinguish parties that call for a determined and assertive policy towards Russia, parties that formulate their views on Russia in a neutral way, as well as parties that call for improvement and pragmatism in bilateral Polish-Russian relations.